Benjamin West and his cat Grimalkin - Henry, Marguerite 1902-; Dennis, Wesley (New York Bobbs-Merrill, 1947)
With his beloved black cat Grimalkin as his constant companion, the young Quaker boy Benjamin West discovers and develops his talent as an artist.
Keywords: West, Benjamin -- 1738-1820 -- Juvenile fiction; West, Benjamin -- 1738-1820 -- Fiction; Artists -- Fiction; Quakers -- Fiction; Cats -- Fiction